Peran Kepala Sekolah Sebagai Supervisor Dalam Meningkatkan Mutu Pembelajaran: Perspektif Abuya Al Maliki (Studi Kasus Di SMP Plus Fityani Pujon Malang) - Alwi Jufri; Dr. Jaudi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore and analyze the role of the school principal as an educational supervisor in enhancing the quality of learning at SMP Plus Fityani Pujon Malang, through an Islamic supervision framework inspired by the pedagogical philosophy of Abuya Prof. Dr. Sayyid Muhammad bin Alawi al-Maliki al-Hasani. The research adopts a descriptive qualitative approach, employing data collection techniques such as participant observation, in-depth interviews, and document analysis.The findings reveal that the principal assumes the role of a murabbī—a spiritual educator and mentor—whose supervision practice transcends conventional technical oversight. Instead, it integrates spiritual, ethical, and emotional dimensions rooted in Islamic values. The supervision process is guided by principles such as ‘adālah (justice), ḥikmah (wisdom), raḥmah (compassion), and tamkīn (empowerment), fostering not only academic excellence but also character development and moral responsibility among teachers and students alike.These results underscore the importance of value-based and spiritually grounded supervision models in Islamic education. Such an approach offers a transformative alternative to bureaucratic or performance-driven supervision, aiming instead to cultivate holistic learning environments that nurture the heart, mind, and soul. The study affirms that educational leadership, when rooted in prophetic values and cultural wisdom, can become a powerful force for institutional growth and ethical reform.